RAGAM HIAS BINATANG DALAM MEDALION - ., Kirno (CORAK, 2012)
Indian - Indonesia culture acculturation played a riddle which still debated until today. Indian cultural influence was strong in Central Java and inversely proportional to the area of East Java. At the temple, the visual form change was easily found where the form of towering slender turned into fat and wide. The concentric form change to chtonis system, human decorations that look realistic style turned into puppets as one of the characteristics of prehistoric cultures. Decorative variety of medallions as one of ornament in Induk Panataran Temple are a visual text that attempts to convey a message. Animal species diversity engraved in Decorative variety of medallions became an evidence of the local genius skills in blending and gathering the Indian cultural influences for the future.Keyword : Ornament, Medallion, Panataran Temple, Local Genius